An altered and more efficient mechanism of CCR5 engagement contributes to macrophage tropism of CCR5-using HIV-1 envelopes - Sterjovski, J.; Roche, M.; Churchill, M.; Ellett, A.; Farrugia, W.; Gray, L.; Cowley, D.; Poumbourios, P.; Lee, B.; Wesselingh, S.; Cunningham, A.; Ramsland, Paul; et al. (Reed Elsevier, 2010)
While CCR5 is the principal coreceptor used by macrophage (M)-tropic HIV-1, not all primary CCR5-using (R5) viruses enter macrophages efficiently. Here, we used functionally-diverse R5 envelope (Env) clones to characterize virus-cell interactions important for efficient CCR5-mediated macrophage entry. The magnitude of macrophage entry by Env-pseudotyped reporter viruses correlated with increased immunoreactivity of CD4-induced gp120 epitopes, increased ability to scavenge low levels of cell-surface CCR5, reduced sensitivity to the CCR5 inhibitor maraviroc, and increased dependence on specific residues in the CCR5 ECL2 region. These results are consistent with an altered and more efficient mechanism of CCR5 engagement. Structural studies revealed potential alterations within the gp120 V3 loop, the gp41 interaction sites at the gp120 C- and N-termini, and within the gp120 CD4 binding site which may directly or indirectly lead to more efficient CCR5-usage. Thus, enhanced gp120-CCR5 interactions may contribute to M-tropism of R5 HIV-1 strains through different structural mechanisms. © 2010 Elsevier Inc.